Understanding a Man-Made Epidemic: The Relation between Historical Asbestos Consumption and Mesothelioma Mortality in Belgium - Van den Borre, Laura; Deboosere, Patrick (TSEG - The Low Countries Journal of Social and Economic History, 2018)
This article discusses (i) the history of asbestos use between 1948 and 2001; (ii) the development of the current epidemic of mesothelioma deaths (1969-2014); and (iii) reasons for the belated government intervention in Belgium. Belgium imported over two billion tonnes of raw asbestos from 1948 until 1998. The current peak in male mesothelioma deaths corresponds to the expansion of the asbestos industry 40 years earlier. Reasons for the delayed government intervention include long latency periods of asbestos-related diseases, faulty communication about health risks, a strong asbestos lobby and an ambivalent government. Public health was sacrificed in favour of industrial development, economic advancement and political gain. The Belgian case further underlines the need for a global ban on asbestos.